Kesulitan Guru IPA SMP Kelas VIII dalam Merencanakan dan Melaksanakan Asesmen - Rita Yanti; Rini Rita T. Marpaung; Berti Yolida (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2017)
This study aims to identify the difficulties of science teachers in planning and implementing an assessment at a private middle school in Labuhan Ratu district, Bandar Lampung City. The samples of the study were all of 8th grade science teachers that were selected with nonprabability sampling technique. This research used descriptive design type. Qualitative data were obtained from interviews of teacher responses and quantitative data were obtained from questionnaires of teacher. The results showed that teachers difficulties in planning the assessment included in sufficient criteria on indicators objectives of the assessment, preparing the instrument, preparing the grid, writing questions based on the grid and writing rules, determining the quality criteria, and compiling the scoring guidelines. The difficulties experienced by teachers in conducting the assessment was sufficient criteria on indicators of the implementation of psychomotor, effective, and cognitive domain. Thus, teachers difficulties in planning and carrying out the assessment was sufficient criteria.Penelitian ini bertujuan mengidentifikasi kesulitan Guru IPA dalam merencanakan dan melaksanakan asesmen pada SMP Swasta se-Kecamatan Labuhan Ratu Kotamadya Bandar Lampung. Sampel penelitian adalah seluruh guru IPA kelas VIII, yang dipilih dengan teknik sampling nonprobability. Desain penelitian ini menggunakan tipe desain deskriptif. Data kualitatif diperoleh dari wawancara pada guru dan data kuantitatif diperoleh dari angket pada guru. Hasil penelitian menunjukkan bahwa kesulitan guru dalam merencanakan asesmen termasuk dalam kriteria cukup pada indikator menetapkan tujuan asesmen, menyusun instrumen, menyusun kisi-kisi, menulis soal berdasarkan kisi-kisi dan kaidah penulisan soal, menentukan kriteria mutu soal, dan menyusun pedoman penskoran. Kesulitan yang dialami oleh guru dalam melaksanakan asesmen termasuk dalam kriteria cukup pada indikator pelaksanaan asesmen ranah psikomotorik, ranah afektif, dan kognitif. Dengan demikian, kesulitan guru dalam merencanakan dan melaksanakan asesmen termasuk kriteria cukup.Kata kunci: kesulitan, melaksanakan asesmen, merencanakan asesmen